THE IMPACT OF SPIDER MODEL OF CORAL TRANSPLANTATION ON FISH ABUNDANCE IN THE WATERS OF BOTUTONUO, GORONTALO PROVINCE - Alhulu, Andeas; Sahami, Femy M.; Hamzah, Sri N (Jurnal Ilmu Kelautan SPERMONDE, 2023)
This study aims to determine the abundance of fish in the recovery location of the coral reef ecosystem in Botutonuo waters, Gorontalo Province. The research was conducted in February - May 2023. The research location consisted of 2 sites, namely site A which had coral transplants with spider coral skeletons and site B which had no transplants (natural coral reefs). Observations were made 3 times with an interval of 2 weeks. Reef fish data was collected using the Underwater Visual Census (UVC) method, with a 50 m x 5 m line transect. Calculation of data using fish abundance rum. The results showed that the number of fish species found in the Botutonuo waters of Gorontalo Province at site A was 89 species with a total individual abundance of 2,429 ind/m2, while at site B there were 69 species with a total individual abundance of 2,054 ind/m2.